Editorial - Kouis, Dimitris (Journal of Integrated Information Management, 2019)
Dear Colleagues, It is with pleasure to announce the new issue of the Journal of Integrated Information Management (JIIM) publication. JIIM is an international, multidisciplinary, blind peer-reviewed journal that publishes research efforts on all aspects and issues regarding Information Science and Integrated Information Management. We are aiming at making JIIM a reputable scientific communication channel, and we are now welcoming submissions for the upcoming journal issues as well as proposals for Special Issues. Your proposal should be no more than five pages and include at least an executive summary, a proper justification why the Special Issue is needed and how it is suitable with the JIIM topics. Special Issues proposals should be sent directly via email the Assistant Editor-in-chief (dkouis@uniwa.gr). Finally, we would like to express our commitment to promoting scientific papers of high-grade quality and that we expect your contribution and active support with remarks and points of improvement.